Macrophage Migration Inhibitory Factor Receptor, CD74, is Overexpressed in Human and Baboon (Papio Anubis) Endometriotic Lesions and Modulates Endometriotic Epithelial Cell Survival and Interleukin 8 Expression. (November 2018) - Nothnick, Warren B.; Falcone, Tommaso; Olson, Mark R.; Fazleabas, Asgerally T.; Tawfik, Ossama W.; Graham, Amanda
CD74 is the primary receptor for macrophage migration inhibitory factor (MIF). Although expression of MIF has been described in endometriotic lesions, the cellular localization and function of the MIF receptor, CD74, are poorly understood. To further explore the role of CD74 in the pathophysiology of endometriosis, we utilized specimens from women with diagnostically confirmed endometriosis, women with no signs or symptoms of endometriosis (controls), and 8 baboons with experimentally induced endometriosis. Compared to eutopic endometrium from women with endometriosis, CD74 transcript expression was significantly increased in endometriotic lesion tissue. Similarly, cellular expression of CD74 was significantly greater in ectopic lesion tissue compared to paired eutopic endometrium, which both expressed greater CD74 expression compared to eutopic endometrium from control patients. Localization of CD74 was predominant to epithelial cells of ectopic and matched eutopic endometrium and was not influenced by the stage of the menstrual cycle. Eutopic endometrium from control patients did not express detectable levels of CD74 protein by immunohistochemistry. This pattern of expression and CD74 protein localization could be recapitulated in endometriotic lesion tissue from baboons with experimentally induced disease. Transfection of the endometriotic epithelial cell lines, 12Z with CD74 short hairpin RNA (shRNA), resulted in a significant decrease in CD74 protein expression, which was associated with a significant reduction in cellular proliferation as well as the expression of the prosurvival cytokine interleukin 8. Together, these data support the hypothesis that CD74 is elevated in endometriotic lesion tissue and may contribute to the pathogenesis of endometriosis by promoting cell survival.